The Use of Social Media Digital Native and Digital Immigrant Muslim Generation in Surabaya - Nurdin, Ali (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
The profile of the Muslim generation can be seen through the map of the use of social media which is divided into two; that is, the native digital generation, the generation born above 1980 when internet technology has evolved and influenced its lifestyle, and digital immigrant; that is, generations born under 1980 who are now still able to use internet technology in their lifestyle. This study aims to explain the tendency of social media to be used, the content of the message delivered, and the reasons for the use of social media by generations of Muslims. Theories used to analyze are technological determinism theory and triple M theory (mass society, mass media, and mass culture). This research uses a quantitative approach with descriptive statistical analysis. The object of his research is the generation of digital native Muslims and digital immigrants in Surabaya with a sample of 150 respondents. The results of this study explain the tendency of the highest percentage of each indicator as follows; the digital native Muslim generation has four social media accounts 31%, digital immigrant has three social media accounts 40%. The digital native Muslim generation uses Instagram social media accounts 23%, digital immigrant uses Facebook 23%, and WhatshaApp 32%. The Muslim generation digital native uses the time to social media in a day for 1 hour 21%, digital immigrant 37%. The Muslim generation digital native has the tendency to convey this type of message on social media with the theme of sharing information 28%, digital immigrant 25%. The tendency of delivering Da'wa messages to the digital native Muslim generation 7%, digital immigrant 73%, the tendency of message content in social media in the digital native Muslim generation with the theme of daily activities as much as 43%. The purpose and reason of using social media the digital native Muslim generation with themed information update 27%, digital immigrant themed information sharing 44%.